Teaching agrobiodiversity - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
A guide to integrate agricultural biodiversity knowledge into education curricula in universities. The curriculum framework has 14 topics central to agrobiodiversity processes, conservation and management.